The relationship between IL-6 expression and ossicular destruction in CSOM with cholesteatoma - Rahayu, Made Lely; Winarti, Ni Wayan; Danastri, I Gusti Ayu Mahaprani; Handayani, Ni Komang Tri Utami; Reniati, Roselina (Oto Rhino Laryngologica Indonesiana, 2025)
Background: Chronic suppurative otitis media (CSOM) is a disease that affects the middle ear, leading to perforation of the tympanic membrane. This condition involves chronic inflammation in the middle ear and mastoid cavity. A CT scan often reveals destruction to the ossicles and cholesteatoma. Purpose: To determine the relationship between increased IL-6 expression and ossicular destruction in CSOM patients with cholesteatoma. Method: This observational analytic study with a cross-sectional comparative design was conducted at the Anatomy Pathology Laboratory of Prof. Ngoerah General Hospital, Denpasar. The study used cholesteatoma tissue paraffin blocks from patients with the dangerous type of CSOM who had undergone tympanomastoidectomy from January 2022 to December 2023. Sampling was carried out through consecutive sampling, which included all cholesteatoma tissue paraffin blocks from patients with the dangerous type of CSOM that met the inclusion criteria, amounting to 17 blocks. Result: This study found a p-value >0.05, indicating no association in the bivariate analysis between the percentage, intensity, and overall score of IL-6 pathology results and ossicular destruction due to cholesteatoma, in CSOM patients. Conclusion: This study concluded that there was no significant relationship between IL-6 expression and hearing bone destruction caused by cholesteatoma in CSOM patients.